REPRESENTATION OF DIFFERENT LYMPHOCYTES' POPULATIONS IN PERIPHERAL BLOOD OF PATIENTS WITH UTERINE MYOMA - Ye. E. Zueva (SPb RAACI, 2014)
Abstract. Uterine myoma is one of the most widespread gynecological pathology among reproductive women older than 30 years. It is known, that often progress of this pathology is associated with genetic and endocrinologic factors. The immune system is not evident still. The aim of this study was to analyze the state of patient's immune system using flow cytometry assessment of different subpopulations of lymphocytes in peripheral blood. We have examined 46 patients with simple and proliferating forms of the myoma, with different variants of clinical symptoms. Absolute and relative content of different subpopulations of lymphocytes was not differed from normal population's standard. Significant differences of B-lymphocytes and natural killers content were observed between groups with simple and proliferating forms of disease. It was shown that metrorrhagia is associated with high level of T-lymphocytes and T-killers. It was noted that decreasing of B-lymphocytes content took place in cases with large number of uterine nodes. Obtained data are not sufficient for complete understanding of the role of immune system in pathogenesis of this disease, but they confirm that using of immunomodulating therapy is expedient for complex treatment of uterine myoma.